(untitled) (Modern education and development, 2025)
The article analyzes the principles of attracting foreign investment in the region. Proposals are developed for the implementation of a number of target tasks for the transition to a "green" economy set out in the Uzbekistan-2030 strategy, and information is provided on investment criteria indicators. The article also discusses the importance of a favorable investment climate and investment activity in ensuring sustainable economic growth, creating jobs and increasing population incomes in the world, and you can also get information about research conducted in this area. There are also extensive works on the priority importance of attracting investment.